Lorazepam in catatonia - past, present and future of a clinical success story - Hirjak, Dusan; Fricchione, Gregory L.; Wolf, Robert Christian; Northoff, Georg (Schizophrenia research, 2024)
The effect of lorazepam in the treatment of catatonia is outstanding and almost immediate. Clinicians are familiar with its effects: mute patients can speak again, akinetic patients can move again and patients with negativism can eat and drink again within usually a short duration of about 10 min to 1-2 h. Fear is often gone after lorazepam administration. While not always effective, the introduction of lorazepam into clinical practice represented a breakthrough and was often life-saving for many patients suffering from catatonia. It is rare to observe such rapid therapeutic effects in other domains of psychiatry. In this narrative review we will briefly look at the past, present and future of lorazepam in the treatment of catatonia. It is gratifying to reflect on the fact that clinicians using the age-old medical practice of observation and empirical treatment succeeded in advancing the management of catatonia 40 years ago. The present evidence shows that the clinical effect of lorazepam in catatonia treatment is excellent and more or less immediate although it remains to be explicitly tested against other substances such as diazepam, zolpidem, clozapine, quetiapine, amantadine, memantine, valproate and dantrolene in randomized clinical trials. In addition, future studies need to answer the question how long lorazepam should be given to patients with catatonia, months or even years? This narrative review promotes the rapid use of lorazepam in the treatment of acute catatonic patients and stipulates further scientific examination of its often impressive clinical effects.